Therapeutic implications of counselling psychologists’ responses to client trauma: an interpretative phenomenological analysis - Merriman, Olivia; Joseph, Stephen (Taylor & Francis, 2016)
The past two decades have seen a surge of interest in the impact of working with trauma survivors on therapists’ psychological well-being. Existing literature assumes that therapists’ strong subjective responses to traumatic material adversely influence the therapeutic process. However, this has not yet been directly researched. Nine counselling psychologists were interviewed regarding the clinical impact of their responses to the disclosure of traumatic material. Interpretative Phenomenological Analysis showed that significant challenges are experienced in the use of self in therapy with trauma survivors, including making sense of horrific human actions, negotiating complex interpersonal dynamics, and responding to ethical dilemmas in therapy. Results emphasised the importance that therapists attached to the development of their therapeutic use of self in therapy with trauma survivors, the value of learning from others and reaching a place of acceptance and hope when working with trauma survivors. Finally, specific training and development implications are proposed.